THE EFFECT OF AWARENESS LEVEL OF PARENTS ON CHILD ABUSE ON PARENT-CHILD RELATIONSHIP - Kiliç, Melek; Günay, Ulviye (Inonu University, 2025)
The study was conducted to determine the effect of parents' awareness of child abuse on the parent-child relationship. This descriptive study was carried out with 406 parents who had children aged 2-7 years and were registered at three family health centers in Kahramanmaraş city center, between February and April 2019. It was determined that being a mother or father did result in any significant difference the Abuse Awareness Scale, the Child-Parent Relationship Scale and its subscale scores of the parents (p>0.05). Additionally, the level of abuse of the parents who were literate or primary school graduates was higher, the level of abuse of the parents decreased as their education level increased, and the level of abuse of the parents decreased as their income level increased. As a result, it was determined that parents' level of awareness about child abuse has a positive effect on the parent-child relationship. © 2025, Inonu University. All rights reserved.
Keywords: Awareness; Child; Child Abuse; Parent; Parent-Child Relationship